Study of crystal structure, lattice strain, and elemental content of natural iron sand nanoparticles synthesized by the coprecipitation method - Duma, Tulus Na; Humaidi, Syahrul; Frida, Erna; Awang Kechik, Mohd. Mustafa; Hamid, Muhammadin; Rianna, Martha; Novita, .; Banurea, Rahmadhani; Mohd Yusof, Norazimah; Azman, Nur Jannah (Faculty of Environment and Resource Studies,Mahidol University, 2025)
This study was conducted to investigate the synthesis of magnetite nanoparticles from iron sand collected from the Bah Bolon River in Indonesia, using the coprecipitation method with NaOH and NH4OH as precipitants. The results showed that based on SEM-EDX (scanning electron microscopy coupled with energy-dispersive x-ray spectroscopy) analysis, the Fe content of the raw iron sand, initially at 34.76%, increased to 45.50% following synthesis with NH4OH, indicating enhanced purity in the final product. SEM observations found average particle sizes of approximately 53 nm for nanoparticles synthesized with NaOH and 20 nm for those synthesized with NH4OH. X-ray diffraction (XRD) analysis confirmed that the synthesized nanoparticles retain the magnetite (Fe3O4) phase with a face-centered cubic (FCC) spinel structure. Crystallite size calculations using the Scherrer equation yielded average crystallite sizes of 80.194 nm for NaOH-synthesized samples and 15.124 nm for NH4OH-synthesized samples, demonstrating that NH4OH favors the formation of smaller crystallites. Lattice strain analysis through the Williamson-Hall method showed positive tensile strain values for all samples, indicating structural tension within the crystal lattice. The NH4OH-synthesized nanoparticles had slightly higher lattice strain, suggesting that synthesis conditions impact both crystallite size and lattice tension. In conclusion, this study demonstrated that NH4OH was more effective than NaOH in producing high-purity, small-crystallite magnetite nanoparticles from natural iron sand, with potential implications for enhanced material properties.